Targeting the NLRP3 inflammasome for calcium oxalate stones: pathophysiology and emerging pharmacological interventions - Boldt, Andrew M.; Di Sole, Francesca (Frontiers in Physiology, 2025)
Kidney stone disease (nephrolithiasis) is a widespread condition affecting millions worldwide, with its prevalence rising due to dietary changes, obesity, and climate-related factors. The formation of kidney stones is driven by urinary solute supersaturation, metabolic abnormalities, and environmental influences. Calcium oxalate stones, the most common type, result from hypercalciuria, hyperoxaluria, and hypocitraturia, often exacerbated by high dietary protein intake and hormonal imbalances such as hyperparathyroidism. A significant complication of kidney stones is their association with chronic kidney disease (CKD). Recurrent stone formation contributes to renal scarring, urinary obstruction, and inflammation, ultimately leading to long-term kidney damage. This review explores the pivotal role of the NLRP3 inflammasome in kidney stone-related inflammation. Activated by calcium oxalate crystals and oxidative stress, NLRP3 triggers the release of pro-inflammatory cytokines (IL-1β and IL-18), exacerbating renal injury and fibrosis. Persistent NLRP3 activation is linked to CKD progression and an increased risk of end-stage renal disease. Emerging therapies targeting NLRP3 offer potential strategies to mitigate kidney stone-induced inflammation and CKD progression. Direct inhibitors such as MCC950 and CP-456773 block inflammasome activation, reducing inflammatory cytokine release. Indirect approaches, including atorvastatin and phenylbutyric acid, address oxidative stress and mitochondrial dysfunction to lower stone formation risk. While these treatments show promise in preclinical studies, further research is needed to validate their clinical efficacy. Future studies should focus on optimizing NLRP3-targeted therapies, assessing their long-term effects on kidney stone prevention and CKD progression. Combining NLRP3 inhibitors with antioxidants may enhance renal protection, providing new avenues for therapeutic intervention.